Wealth gradient-based divergence in the prevalence of underweight among women by marital status in Quoc Oai district, Vietnam. Issue 1 (1st January 2018) - Heo, Jongho; Yu, Soo-Young; Yi, Jinseon; Nam, You-Seon; Son, Dinh Thai; Oh, Juhwan; Lee, Jong-Koo
ABSTRACT: Background : The prevalence of underweight is high among women in Asian countries, despite nutritional changes in the region. Previous studies have demonstrated independent associations between female body weight, marital status and economic status. However, few studies have investigated possible interaction between marital and economic status in relation to Asian women's body weight. Objective : This study aimed to test associations between household wealth, marital status and underweight among women living in the Quoc Oai district of Vietnam and to identify wealth–marital status interaction in relation to body weight in these women. Methods : Data from 1087 women aged 19–60 years were collected via a baseline community survey conducted in the Quoc Oai district of Hanoi, Vietnam, in 2016. Underweight was defined using an Asian-specific body mass index cut-off (<18.5 kg/m 2 ). Marital status was dichotomized into 'never married' and 'ever married.' Economic status was measured using household wealth index quintiles. Multivariable logistic regressions tested association between wealth and underweight after adjusting for marital status and other confounders. An interaction term (wealth index*marital status) was fitted to determine whether the association between wealth and body weight is modified by marital status. Results : Our results show that underweight was independently associated with a wealth status (odds ratio [OR]: 0.88, 95% confidence interval [CI]: 0.79–0.98, p  = 0.026) and ever-married status (OR: 0.50, 95% CI: 0.34–0.75, p  = 0.002). A significant interaction effect (OR: 0.67, 95% CI: 0.50–0.90, p  = 0.010) indicated that wealthy married women were less likely to be underweight, whereas wealthy never-married women were more likely to be underweight. Conclusions : Our results suggest that the interaction between wealth and marital status has divergent effects on underweight among Asian women. Interventions to reduce underweight among Asian women should simultaneously consider economic and marital status.